Increased Expression of Macrophage Migration Inhibitory Factor in the Nucleus of the Solitary Tract Attenuates Renovascular Hypertension in Rats - Barbosa, Rafaela Moreira [UNESP]; Speretta, Guilherme F. [UNESP]; Martins Dias, Daniel Penteado; Ruchaya, Prashant Jay [UNESP]; Li, Hongwei; Menani, Jose Vanderlei [UNESP]; Sumners, Colin; Colombari, Eduardo [UNESP]; Colombari, Debora S. A. [UNESP] (Oxford Univ Press, 2017)
BACKGROUND Macrophage migration inhibitory factor (MIF) is an intracellular inhibitory regulator of the actions of angiotensin II in the central nervous system. Renovascular hypertensive 2-kidney, 1-clip (2K1C) rats have an increased activity of the renin-angiotensin system and a decrease in baroreflex function compared to normotensive (NT) rats. In the present study, we tested the effects of MIF overexpression within the nucleus of the solitary tract (NTS), a key brainstem region for cardiovascular regulation, on the development of hypertension, on baroreflex function, and on water and food intake in 2K1C rats. METHODS Holtzman NT rats received a silver clip around the left renal artery to induce 2K1C hypertension. Three weeks later, rats were microinjected in the NTS with AAV2-CBA-MIF, to increase the expression of MIF, or with the control vector AAV2-CBA-enhanced green fluorescent protein. Mean arterial pressure (MAP) and heart rate were recorded by telemetry. Baroreflex function was tested, and water and food intake were also measured. RESULTS Increasing MIF expression in the NTS of 2K1C rats attenuated the development of hypertension, reversed the impairment of baroreflex function, and reduced the increase in water intake. In contrast to 2K1C rats, similar increases in MIF expression in the NTS of NT rats produced no changes in baseline MAP, baroreflex function, or water intake. CONCLUSIONS These results indicate that an increased expression of MIF within the NTS attenuates the development of hypertension and restores the baroreflex function in 2K1C rats.
Keywords: angiotensin II; AT1 receptor; baroreflex; blood pressure; brainstem; hypertension; 2K1C